PENENTUAN OPERATOR KARTU SELULER TERBAIK MENGGUNAKAN METODE AHP(ANALITYCAL HIERARCHY PROCESS) - Rizaldi Rizaldi (Universitas Asahan, 2017)
Abstract - The role of telecommunications technology is very important, especially in changing people's lives. The development of technology in the field of communication and information can now be enjoyed by various layers of society, starting from the upper layer, middle layer or lower layer even though the results are not satisfactory. The research entitled